Lichen planus verrucosus in an association with vitiligo - Petrosian, R.; Liesionyte, K.; Petkevicius, A.; Kucinskiene, V.; Makstiene, J.; Valiukeviciene, S. (Aktuelle Dermatologie, 2015)
Lichen planus (LP) is a chronic inflammatory disease with characteristic skin lesions and histological findings. Hypertrophic lichen planus, also known as lichen planus verrucosus, is a subtype of lichen planus. Lichen planus verrucosus is clinically characterized by pruritic symmetric hyperkeratotic plaques of red, yellow-gray, red-brown or purplish-grey colour, usually located on the pretibial or perimalleolar areas, less often on the arms or trunk. Lichen planus affects about 0.5 – 1 % of the population. Hypertrophic lichen planus is a less common form of lichen planus. It accounts for 4.7 % of lichen planus cases. The disease has a chronic course, and it is often resistant to local and systemic treatment. This article describes a rare lichen planus verrucosus form in association with vitiligo.